Sexually transmitted infections—Research priorities for new challenges - Low, Nicola (PLoS Med, 2017)
In an Editorial, Guest Editors Nicola Low and Nathalie Broutet discuss the Collection on sexually transmitted infections in the context of research priorities in the field.